TLR4 links innate immunity and fatty acid–induced insulin resistance - Hang Shi; Maia V. Kokoeva; Karen Inouye; Iphigenia Tzameli; Huali Yin; Jeffrey S. Flier (The Journal of Clinical Investigation, 2006)
TLR4 is the receptor for LPS and plays a critical role in innate immunity. Stimulation of TLR4 activates proinflammatory pathways and induces cytokine expression in a variety of cell types. Inflammatory pathways are activated in tissues of obese animals and humans and play an important role in obesity-associated insulin resistance. Here we show that nutritional fatty acids, whose circulating levels are often increased in obesity, activate TLR4 signaling in adipocytes and macrophages and that the capacity of fatty acids to induce inflammatory signaling in adipose cells or tissue and macrophages is blunted in the absence of TLR4. Moreover, mice lacking TLR4 are substantially protected from the ability of systemic lipid infusion to (a) suppress insulin signaling in muscle and (b) reduce insulin-mediated changes in systemic glucose metabolism. Finally, female C57BL/6 mice lacking TLR4 have increased obesity but are partially protected against high fat diet–induced insulin resistance, possibly due to reduced inflammatory gene expression in liver and fat. Taken together, these data suggest that TLR4 is a molecular link among nutrition, lipids, and inflammation and that the innate immune system participates in the regulation of energy balance and insulin resistance in response to changes in the nutritional environment.